Entrepreneur’s Human Capital and Business Model Innovation: The Meditation Role of Access to Start-Up Resources - Tran, Nha Ghi (http://ijims.ms.tku.edu.tw/main.php, 2021)
Based on human capital theory, this study aims to explain start-up resources formation and business model innovationThe study examined the eﬀect of entrepreneur’s human capital (including managerial skills and entrepreneurial skills) on business model innovation via access to start-up resources as a mediator. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was conducted with the size sample of 220 founders/ co-founders of start-up ﬁrms in Vietnam. The research results supported the positive links from managerial skills and entrepreneurial skills to business model innovation through the mediating mechanism of access to start-up resources. The study explored the meditation role of access to start-up resources between entrepreneur’s human capital and business model innovation. In addition, the results provide practical value to entrepreneurs in improving managerial skills and entrepreneurial skills in order to facilitate the access to outside support resources and promote business model innovation. Finally, the study suggests some managerial implications for entrepreneurs, research limitations and further research directions.